Thin film photoelectrodes for solar water splitting. (22nd January 2019) - He, Yumin; Hamann, Thomas; Wang, Dunwei
Abstract : This review provides a comprehensive overview of the fabrication, development and application of thin-film photoelectrodes. Abstract : Photoelectrochemical (PEC) water splitting has been intensively studied in the past decades as a promising method for large-scale solar energy storage. Among the various issues that limit the progress of this field, the lack of photoelectrode materials with suitable properties in all aspects of light absorption, charge separation and transport, and charge transfer is a key challenge, which has attracted tremendous research attention. A large variety of compositions, in different forms, have been tested. This review aims to summarize efforts in this area, with a focus on materials-related considerations. Issues discussed by this review include synthesis, optoelectronic properties, charge behaviors and catalysis. In the recognition that thin-film materials are representative model systems for the study of these issues, we elected to focus on this form, so as to provide a concise and coherent account on the different strategies that have been proposed and tested. Because practical implementation is of paramount importance to the eventual realization of using solar fuel for solar energy storage, we pay particular attention to strategies proposed to address the stability and catalytic issues, which are two key factors limiting the implementation of efficient photoelectrode materials. To keep the overall discussion focused, all discussions were presented within the context of water splitting reactions. How the thin-film systems may be applied for fundamental studies of the water splitting chemical mechanisms and how to use the model system to test device engineering design strategies are discussed.